Successful endovascular therapy for cerebral venous sinus thrombosis accompanied by heparin-induced thrombocytopenia - Fukushima, Yoshihisa (Interv Neuroradiol, 2020)
INTRODUCTION: Heparin-induced thrombocytopenia (HIT) is an immune-mediated complication of heparin exposure. A limited number of studies have reported cerebral venous sinus thrombosis accompanied by heparin-induced thrombocytopenia. Here, we present a case of successful endovascular therapy (EVT) without periprocedural heparinization in this situation. CASE PRESENTATION: A 47-year-old woman taking an oral contraceptive was admitted to our hospital with severe headache to be diagnosed as cerebral venous sinus thrombosis. Initially, she got improved by medical treatment with intravenous unfractionated heparin. However, she rapidly developed disturbance of consciousness and right hemiplegia due to cerebral venous sinus thrombosis accompanied by heparin-induced thrombocytopenia on the 14th hospital day. She underwent emergent EVT by immediate conversion of anticoagulation from heparin to argatroban. Despite a large clot burden, sufficient recanalization and anterograde venous drainage were re-established by combined EVT including aspiration, balloon sinoplasty, and local thrombolysis with urokinase infusion. She got improved immediately after the intervention and discharged home without any neurological sequelae after two months. CONCLUSION: This unique case of cerebral venous sinus thrombosis worsened by occurrence of heparin-induced thrombocytopenia during the treatment finally resulted in excellent outcome highlights effectiveness of emergent endovascular intervention for critical cerebral venous sinus thrombosis resistant to initial medical treatment and of immediate establishment of effective anticoagulant strategy for both of heparin-induced thrombocytopenia and cerebral venous sinus thrombosis. Neuroendovascular therapy for cerebral venous sinus thrombosis using alternative argatroban to heparin for periprocedural anticoagulation might be safe and feasible.